(untitled) (Al-Aasar, 2026)
The study investigates the use of meta-discourse markers in political blogs. Specifically, it examines the frequency and distribution of interactive meta-discourse markers to express writer stance and engage readers, and compares the relative prominence of interactive and interactional meta-discourse markers within the selected blogs. The study adopts a corpus-based mixed-method design to investigate the use of meta-discourse markers in political blogs. The data sample for the study consists of twelve (12) political blogs published in The Express Tribune and The News of Pakistani English newspapers. The paper employs Hyland’s (2005) interpersonal model of meta discourse as the guiding framework to examine organisational discourse, stance expression, and reader engagement among bloggers. It was found that interactive markers are more frequent, including transitions, frame markers, code glosses, and endophoric markers, and therefore emphasise their importance in argument structuring and directing the reader in the process of understanding political talks. Interactional markers such as hedges, boosters, attitude markers, self-mentions, and engagement markers are also popular in bloggers’ attempts to express evaluation, persuasion, and interpersonal involvement. The comparison shows stylistic differences in the newspaper blogs, with the News blogs employing more regularly than the Express Tribune. The paper concludes that for successful political blogging combination of textual structuring and interpersonal interaction is necessary, offering essential insights into discourse practices in Pakistani English print media.